The Growth of Takaful Industry in the Muslim World: A Comparative Case Study between Malaysia and Saudi Arabia - Assane Ossofo; Hartinie Abd Aziz (Yuridika, 2026)
Despite recent decades' growth of the industry's Takaful importance in Muslim-majority states, comparative studies on its growth across the regions are limited. Although Takaful has a modest market share on a global scale, it has shown appreciable growth within states like Malaysia, UAE, Kuwait, Saudi Arabia, Oman, Morocco, and Bahrain. Islamic Finance Development Indicator (2018) estimated that Takaful would be USD 72 billion by 2023. Through a library-based qualitative research, growth of the sector in Saudi Arabia and Malaysia during 2017–2020 has been compared using key drivers of growth identification. The findings suggest that there has been considerable industry growth both countries, facilitated by the demand from the majority populations for shariah-compatible options for traditional insurance products. Religious commitments, demographic alignments, and supportive institutional arrangements have come out as the decisive enablers for growth. The research brings out how each of these factors contributes uniquely with national specificities, modifying Takaful growth paths differently across the two countries. By comparing Saudi Arabia's market sophistication with that of Malaysia's innovative regulation, the research highlights socio-cultural and structural dynamics' role for Islamic finance growth. This study helps to apprehend how faith-based considerations and institutional malleability shape the growth of Takaful across different contexts, guiding policymakers and industry actors to harness massive growth opportunities for their markets.